Translation strategies used by Ly Lan in translating neologisms in the fourth volume of “The Harry Potter” series = Chiến lược dịch từ mới Lý Lan sử dụng trong tập bốn của bộ truyện “Harry Potter” - Trần, Thị Hoan (2021)
The thesis aims to figure out the characteristics of neologisms in the story “Harry Potter and the Goblet of Fire” and the translation procedures applied by Ly Lan in its Vietnamese translation “Harry Potter và Chiếc Cốc Lửa” to translate English invented words. The study mainly involved observation of English source text to identify new words and expressions and then the researcher classifed them based on Newmark’s taxonomy integrated with word-formation mechanisms. In addition, Vietnamese translations of English neologisms are dissected to work out translation strategies that Vietnamese translator – Ly Lan used to deal with novel words. In brief, the majority of new words in the fourth volume in “Harry Potter” series are new forms which experience changes in forms and compounding is the dominant word-formation process in creation of neologisms. Ly Lan utilizes numerous strategies to translate new words in which “Literal translation” and “Loan translation” are preferred ones.